Virtual hydrate screening and coformer selection for improved relative humidity stability. Issue 28 (28th July 2015) - Abramov, Yuriy A.
<x xml:space="preserve">Abstract</x> The descriptors were determined, which can be most efficiently applied to virtual screening in order to provide answers to the following questions: 1) what is the propensity to form a solid state hydrate of a pharmaceutical compound, and 2) which coformer would provide for the highest stability with respect to relative humidity conditions?